English speaking materials for the tenth grade students based on the 2017 revised edition of the 2013 Curriculum - Ribut Diyari Nindyana (Universitas Sarjanawiyata Tamansiswa, 2019)
The purpose of this study is (1) to develop supplementary English-speaking materials for the students of SMKN 1 Tanjungsari grade X based on the 2013 Curriculum, (2) to describe the effectiveness of the supplementary English-speaking material for the students of SMKN Tanjungsari grade X in developing their speaking skill. The research belongs to Educational research and Development (R&D) using a simplified six steps of Borg and Gall’s model (1983). The six steps are as follows. (1) Research and information collecting were conducted by performing document analysis, class observation, interview, product testing, as well as experts’ judgement, (2) planning and drafting were conducted following Nation and Macallister (2010), (3) Draft revision by expert, (4) Field testing was conducted in Nautica class A of the X grade of SMKN 1 Tanjungsari, (5) Revision, and (6) Final product. The finding shows that (1) supplementary materials which were developed in this research fulfill the criteria of R&D model. It is necessary to provide speaking materials which were needed for the students of SMKN 1 Tanjungsari who faced the problem in speaking skill. The product of the research also fulfills the teacher’ needs as the materials which are not covered in the recently used textbook can be found in this supplementary material but the focus is in speaking. (2) The effectiveness of the supplementary speaking materials shows it is helpful towards the students in developing their speaking skill which is very needed in working world. The supplementary of speaking materials provides additional learning resources for students as well as the teacher to teach.